BMPR2 Mutation and Metabolic Reprogramming in Pulmonary Arterial Hypertension. Issue 1 (6th January 2023) - Cuthbertson, Iona; Morrell, Nicholas W.; Caruso, Paola
Abstract : Abstract: Pulmonary arterial hypertension forms the first and most severe of the 5 categories of pulmonary hypertension. Disease pathogenesis is driven by progressive remodeling of peripheral pulmonary arteries, caused by the excessive proliferation of vascular wall cells, including endothelial cells, smooth muscle cells and fibroblasts, and perivascular inflammation. Compelling evidence from animal models suggests endothelial cell dysfunction is a key initial trigger of pulmonary vascular remodeling, which is characterised by hyperproliferation and early apoptosis followed by enrichment of apoptosis-resistant populations. Dysfunctional pulmonary arterial endothelial cells lose their ability to produce vasodilatory mediators, together leading to augmented pulmonary arterial smooth muscle cell responses, increased pulmonary vascular pressures and right ventricular afterload, and progressive right ventricular hypertrophy and heart failure. It is recognized that a range of abnormal cellular molecular signatures underpin the pathophysiology of pulmonary arterial hypertension and are enhanced by loss-of-function mutations in the BMPR2 gene, the most common genetic cause of pulmonary arterial hypertension and associated with worse disease prognosis. Widespread metabolic abnormalities are observed in the heart, pulmonary vasculature, and systemic tissues, and may underpin heterogeneity in responsivity to treatment. Metabolic abnormalities include hyperglycolytic reprogramming, mitochondrial dysfunction, aberrant polyamine and sphingosine metabolism, reduced insulin sensitivity, and defective iron handling. This review critically discusses published mechanisms linking metabolic abnormalities with dysfunctional BMPR2 (bone morphogenetic protein receptor 2) signaling; hypothesized mechanistic links requiring further validation; and their relevance to pulmonary arterial hypertension pathogenesis and the development of potential therapeutic strategies.